2018
DOI: 10.1016/j.jece.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium removal by a low-cost magadiite-based material: Characterization and sorption applications

Abstract: Na-magadiite-based materials have been studied for Cd(II) removal from waters  The sorbents were characterized with different techniques (XRD, FTIR, TGA, SEM-EDX)  The introduction of Cyanex-272 into the interlayers of Na-Magadiite was studied  The introduction of Cyanex-272 improves the selectivity towards cadmium ions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…In the past decades, several efficient ways to treat wastewater containing organic and inorganic pollutants have been considered as one of the important topics in environmental science [1][2][3][4][5]. Chlorinated organic compounds (e.g., dioxins, polychlorophenols) are known as significant environmental pollutants, because these compounds have great resistance to biological degradation processes and affect serious health problems (e.g., nervous or respiratory systems) via the bioaccumulation of organisms in the ecosystem [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, several efficient ways to treat wastewater containing organic and inorganic pollutants have been considered as one of the important topics in environmental science [1][2][3][4][5]. Chlorinated organic compounds (e.g., dioxins, polychlorophenols) are known as significant environmental pollutants, because these compounds have great resistance to biological degradation processes and affect serious health problems (e.g., nervous or respiratory systems) via the bioaccumulation of organisms in the ecosystem [6].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of pH is a key factor on the sorption process. The pH may affect the speciation of the metals through formation of complex molecules [37], and the protonation of carboxylic groups present in the alginate chains (the mannuronic and guluronic blocks; i.e., M and G-blocks) [38]. The experiments were carried out over a pH range from 3 to 12; the results in Figure 2a demonstrated that higher sorption efficiency was obtained on decreasing the proton concentration of the solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Magadiite (MAG) is a kind of layered silicate material [19,20] that possesses a large amount of potentially exchangeable hydrated sodium ions between its layers [21]; for this reason, MAG has unique properties, such as high surface area, good ion exchange, and expansion [22,23]. MAG showed excellent adsorption performance on heavy metal ions and organic pollutants [24,25,26], although it was difficult to separate from the water after adsorption. Fe 3 O 4 is a typical superparamagnetic nanoparticle with chemical stability, large specific surface area, easy separation, and good biocompatibility [27,28,29,30], but it is also easy to agglomerate in the aqueous system to influence on its adsorption properties because of its small particle size [31].…”
Section: Introductionmentioning
confidence: 99%